Entrepreneurial behaviour of Hi-Tech farmers in Kerala - Shilpa Karat (Department of Agricultural Extension, College of Horticulture, 2019)
The conventional farming system in Kerala witnessed a path breaking change in the recent years with the adoption of hi-tech farming, which is a promising venture for the educated youth and part time farmers who are progressively attracted to agriculture. Keeping in view of this increasing acceptance of hi-tech farming, Kerala State Agriculture Development and Farmers Welfare Department has initiated many programs to promote protected cultivation and precision farming in the state. However, the success of hi-tech farming is determined by crucial aspects such as the entrepreneurial attributes and marketing behavior of the farmer. With this background, the present study was undertaken to analyse the entrepreneurial and marketing behavior of the hi-tech farmers, their linkages with other sectors, constraints faced by them along with a SWOC analysis of the hi-tech farming sector. The results of the study would be greatly helpful for the policy makers, government and extension workers in formulating plans for hi-tech farming sector in Kerala. A total of 60 hi-tech farmers, 30 each of polyhouse and open precision were selected from Trissur and Palakkad districts through multistage sampling method. Entrepreneurial behavior was quantified using Entrepreneurial Behavior Index. The index was found to be higher (68.98) for open precision farmers compared to that of polyhouse farmers (64.87). Indices were formed separately for each of the nine selected dimensions of entrepreneurial behavior viz., innovativeness, decision making ability, achievement motivation, risk taking ability, planning ability, cosmopoliteness, self-confidence and information seeking behavior. Information seeking behavior gained highest index for both polyhouse and open precision farmers. Further, Mann-Whitney U test was performed to ascertain significance of the difference between two groups and it was found that the two groups were significantly different in their entrepreneurial behavior with respect to decision making ability, achievement motivation and self-confidence. The marketing behavior of hi-tech famers was studied for polyhouse and open precision farmers. The components selected were marketed surplus, marketing channels, distance to market, mode of transport, price satisfaction, access to market information, access to storage and post-harvest handling or value addition. Since 12 of the 30 polyhouse farmers had quit commercial production, only 18 polyhouse farmers were considered in studying the marketing behavior. The results of Discriminant Function Analysis revealed that there was significant XXV